2014
DOI: 10.5433/1679-0359.2014v35n4suplp2501
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic evaluation of cardiac silhouette in healthy Maine Coon cats

Abstract: Determining the size of the heart is important for evaluating cardiac patients, because the increase of the cardiac silhouette in the chest radiography can be indicative of heart disease. The vertebral heart size (VHS) method is useful because it allows objective assessment of the limits of cardiac silhouette, and can help assess cardiomegaly and document changes in heart size in response to treatment or disease progression. The aim of this study was to compare VHS values of Maine Coon cats (MCC) with values c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…It was determined that the VHS values we obtained from the thorax radiograph in this study conducted with the Persian cats were at 8.18 and 8.15 (8.16 ± 0.44 on average for 30 cats) vertebral level, respectively, in lateral radiograph and they were 8.67 and 8.81 in DV and VD radiographs for the male and female cat (8.74 ± 0.58 on average for 28 cats) vertebral level, respectively, and it was observed that they were higher than the VHS values of the other cat breeds specified in the literature (Litster & Buchanan, 2000a, 2000b; Ghadiri et al., 2008; Guglielmini et al., 2014; Oliveira et al., 2014; Bîrsan et al., 2016). Similarly, it has been emphasized in the study conducted on the vertebral heart size of pug, Boston terrier and bulldog breed dogs (Jepsen‐Grant et al., 2013) that the reason behind why VHS values of these breeds were higher than the VHS values reported by Buchanan and Bücheler (1995) for dogs (9.7 ± 0.5) may be due to the fact that these breeds were brachycephalic breeds.…”
Section: Discussionmentioning
confidence: 85%
“…It was determined that the VHS values we obtained from the thorax radiograph in this study conducted with the Persian cats were at 8.18 and 8.15 (8.16 ± 0.44 on average for 30 cats) vertebral level, respectively, in lateral radiograph and they were 8.67 and 8.81 in DV and VD radiographs for the male and female cat (8.74 ± 0.58 on average for 28 cats) vertebral level, respectively, and it was observed that they were higher than the VHS values of the other cat breeds specified in the literature (Litster & Buchanan, 2000a, 2000b; Ghadiri et al., 2008; Guglielmini et al., 2014; Oliveira et al., 2014; Bîrsan et al., 2016). Similarly, it has been emphasized in the study conducted on the vertebral heart size of pug, Boston terrier and bulldog breed dogs (Jepsen‐Grant et al., 2013) that the reason behind why VHS values of these breeds were higher than the VHS values reported by Buchanan and Bücheler (1995) for dogs (9.7 ± 0.5) may be due to the fact that these breeds were brachycephalic breeds.…”
Section: Discussionmentioning
confidence: 85%